Impact of Concomitant Statin Use on Survival Outcomes in Non-Small Cell Lung Cancer Patients Treated with Immune Checkpoint Inhibitors: A Systematic Review and Meta-Analysis - Alvim Pereira, Rafael; Figueiroa, Pedro; Lenz, Gabriel; Tumelero, Milena; Schwengber, Wallace Klein (Asian Pacific Journal of Cancer Nursing, 2026)
Background: Preclinical and observational evidence suggests that statins may enhance the efficacy of immune checkpoint inhibitors (ICIs) in cancer, including non-small cell lung cancer (NSCLC). However, existing meta-analyses have included mixed cancer types or lacked updated data. We conducted a comprehensive, NSCLC-specific meta-analysis to evaluate the association between statin use and clinical outcomes in ICI-treated patients. Methods: We systematically searched PubMed, Embase, and Cochrane Library for studies published up to May 2025 that assessed statin use in NSCLC patients receiving ICIs. Outcomes included overall survival (OS), progression-free survival (PFS), objective response rate (ORR), and immune-related adverse events (IRAEs). Random-effects models were used to pool hazard ratios (HRs) or odds ratios (ORs). Subgroup analyses were performed based on statistical adjustment (multivariate vs. univariate) and ICI type. Results: A total of 10 retrospective studies comprising 3,761 patients were included. Statin use was associated with improved OS (HR: 0.83, 95% CI: 0.71–0.98, P = 0.03, I² = 36%) and a non-significant trend toward better PFS (HR: 0.83, 95% CI: 0.68–1.02, P = 0.08, I² = 62%). Statin use significantly increased the ORR (OR: 2.91, 95% CI: 1.72–4.94, P < 0.0001), without a statistically significant rise in IRAEs (OR: 1.59, 95% CI: 0.76–3.34, P = 0.22). Subgroup analysis revealed that OS benefit was primarily driven by studies using multivariate adjustment (HR: 0.73, 95% CI: 0.61–0.87), with no significant effect observed in univariate studies. Conclusions: This NSCLC-focused meta-analysis suggests that statin use is associated with improved survival and response in patients treated with ICIs, without a clear increase in toxicity. These findings support further prospective studies to explore the immunomodulatory potential of statins in lung cancer.